Analisis tingkat kelelahan kerja terhadap produktivitas karyawan - Gustara, Rizki Asih; Amini, Aisah; Octavia, Mayang Dwi; Astuti, Yeni Ayu (Jurnal Kesmas Prima Indonesia, 2023)
One of the body's defense systems, namely fatigue, allows the body to recover after rest and avoid additional injury. Fatigue due to continuous work will cause the health of employees to decline, causing work accidents. There are many different elements that can lead to workplace burnout, including the work environment, internal factors, external factors, workplace factors, and individual issues. productivity is influenced by three factors, namely workload, work capacity, and additional burden due to the work environment. Workload is usually related to physical, mental and social loads that affect the workforce. The purpose of this research is to examine how employee productivity is affected by the level of work fatigue. Using the terms burnout and work productivity, a Google Scholar search is conducted for related material. According to the 8 articles collected, work fatigue is closely related to work productivity, so management measures and related regulations are needed to reduce the burden on employees, provide assistance to those in need, and inspire and motivate workers to increase employee productivity.